Direct comparisons of effectiveness and safety of treatment with Apixaban, Dabigatran and Rivaroxaban in atrial fibrillation. Issue 185 (January 2020) - Jansson, M.; Själander, S.; Sjögren, V.; Renlund, H.; Norrving, B.; Själander, A.
Abstract: Introduction: Direct oral anticoagulants (DOACs) have been proven non-inferior or superior to warfarin in preventing stroke and systemic embolism, with a lower risk of major hemorrhage, in patients with non-valvular atrial fibrillation (NVAF). We sought to investigate whether effectiveness and safety differs among apixaban, rivaroxaban and dabigatran. Materials and methods: Patients with newly initiated DOAC treatment were identified from the Swedish anticoagulation quality registry, ranging from January 1, 2013 to December 31, 2015. Patients were assigned to apixaban, dabigatran or rivaroxaban cohorts based on initiated DOAC and dose (standard or reduced). Baseline characteristics and endpoints were retrieved from validated Swedish quality registers and the National Patient Registry. Cohorts were matched using full optimal matching and directly compared. Results: A total of 25, 843 NVAF patients were included. Patients treated with standard dose apixaban or dabigatran had lower risk of major bleeding than patients treated with rivaroxaban, HR 0.69 (95% CI 0.54–0.88) and HR 0.64 (95% CI 0.48–0.87). Regarding reduced dose, patients treated with apixaban had lower risk of major bleeding than those treated with dabigatran or rivaroxaban, HR 0.62 (95% CI 0.44–0.88) and HR 0.45 (95% CI 0.33–0.61). In reduced dose, patients treated with dabigatran had the lowest all-cause mortality. No differences in effectiveness were found. Conclusions: In this large real-world NVAF cohort, direct comparisons show a favorable bleeding risk profile for dabigatran and apixaban in standard dose, and for apixaban in reduced dose. No differences in effectiveness were found. This study confirms previous indirect DOAC comparisons. Further studies are needed. Highlights: Direct oral anticoagulant (DOAC) treatment prevents embolism in atrial fibrillation patients. Effectiveness and safety discrepancies among different DOACs are not well understood. Standard dose apixaban and dabigatran carries lower bleeding risk than rivaroxaban. Reduced dose apixaban carries lower bleeding risk than rivaroxaban and dabigatran. No statistically significant differences in effectiveness were found.